Gender Dynamics and Non-Farm Income Diversification: A Quantitative Study in Rural Pakistan - Sahil Fatima; Nazia Bano; Mohsan Iqbal; Dr. Hafiz Abdul Rehman Saleem (Indus Journal of Social Sciences, 2025)
Talents other than farm for income distribution are a vital strategy for socio-economic resilience in rural households, particularly in developing countries like Pakistan. The paper inspects gendered participation in non-farm projects and their impact on domestic welfare. The primary data has 290 rural households with 54.79% dependents, this is quantitative research which implements statistical analysis, visual highlights and linear regression model to assess determinants and income disparities. The paper is based on query How gender disparities in income contributions and access to resources effect households in Pakistan? Pakistan is enriched with patriarchal society, where men have been destined to opportunities for economic development since ages. On the other hand, women are largely confined to domestic roles. Despite this, women in small and medium-sized enterprises are found of having strong decision-making abilities and righteous contributions to household income. Rural women face lots of challenges, some include access constraints to education, finances, and entrepreneurial training. Empowering women and enhancing their participation in non-farm activities is essential to creating a balanced economy where both men and women contribute effectively to national development. Since 2006, Pakistan has increased gender parity by 0.5%. However, Southern Asia collectively got 63.4% of it.